The Formation and characteristics of university students' values in Mongolia (Mongolian Journal of Humanities and Social Sciences, 2025)
This article examines the current situation of Mongolian university students the country’s foundational demographic group by comparing their challenges, value formation, and characteristics. With the transition from a socialist system, which emphasized collective living, public ownership, cooperative labor, and social discipline, to a democratic and market-based society, people’s values and priorities have shifted significantly. In this open, market-oriented society that followed socialism, the values and principles of young people have undergone considerable changes. A study on students’ values revealed that the most important aspects they prioritize are: 1. Upbringing and morality (21.5%) 2. Education and knowledge (18.6%) 3. Patriotism (10.8%) 4. Freedom (10.3%) 5. Money (8.9%).This article presents the key findings of a study that surveyed 5,638 university students from various regions of Mongolia who are currently studying in the capital city, using a random sampling method.Монгол дахь оюутан залуучуудын үнэт зүйлсийн төлөвшил, онцлогХураангуй: Тус өгүүлэлд Монгол Улсын хүн амын суурь бүлэг болох оюутан залууст тулгамдаж буй асуудал, үнэт зүйлсийн төлөвшил, онцлогийг харьцуулан авч үзсэний үндсэн дээр өнөөгийн нөхцөл байдлыг тодорхойлсон болно.Нийтээр аж төрөх ёс, бүх нийтийн өмч, хамтын хөдөлмөр, нийгмийн сахилга дэг журмыг эрхэмлэж ирсэн социалист тогтолцооноос ардчилсан, зах зээлийн нийгэмд шилжсэнээр хүмүүсийн үнэт зүйл, эрхэмнэлийн тогтолцоо өөрчлөгдсөн. Социализмын дараах нээлттэй, зах зээлийн нийгэмд амьдарч залуучуудын үнэт зүйл, эрхэмнэл үлэмж өөрчлөгдөж байна. Оюутнуудын дунд явуулсан үнэт зүйлийн судалгаагаар нэгд хүмүүжил, ёс суртахуун (21.5%), хоёрт эрдэм боловсрол (18.6%), гуравт эх орон (10.8%),  дөрөвт эрх чөлөө (10.3%), тавд мөнгө (8.9%)-ийг эрхэмлэн дээдлэж явдгаа илэрхийлжээ.Энэхүү өгүүлэлд Монгол Улсын өнцөг булан бүрээс нийслэл хотод суралцаж буй 5638 оюутан залуучуудыг санамсаргүй түүврийн аргыг хамруулан судалж, гол үр дүнг хураангуйлан хүргэж байна.Түлхүүр үг: Нийгэм-хүн ам зүйн бүлэг, амьдралын хэв маяг, тулгамдаж буй асуудал, үнэт зүйл, эрэмбэ